2010
DOI: 10.1088/0031-9155/55/7/001
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent tissue-specific exposure of cell phone users

Abstract: The peak spatial specific absorption rate (SAR) assessed with the standardized specific anthropometric mannequin head phantom has been shown to yield a conservative exposure estimate for both adults and children using mobile phones. There are, however, questions remaining concerning the impact of age-dependent dielectric tissue properties and age-dependent proportions of the skull, face and ear on the global and local absorption, in particular in the brain tissues. In this study, we compare the absorption in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
105
1
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(111 citation statements)
references
References 40 publications
3
105
1
2
Order By: Relevance
“…Model families of phantoms of various ages and both sexes are now available (Christ et al, 2010a;Lee et al, 2010) and various studies of the SAR distribution in children of different ages, pregnant women and foetuses have been published (Christ et al, 2010b;Dimbylow & Bolch, 2007;Dimbylow, Nagaoka & Xu, 2009;Uusitupa et al, 2010). Further work, including modelling the SAR distribution at different gestational stages, is being pursued in several countries.…”
Section: Further Work On Dosimetric Models Of Children Of Different Amentioning
confidence: 99%
“…Model families of phantoms of various ages and both sexes are now available (Christ et al, 2010a;Lee et al, 2010) and various studies of the SAR distribution in children of different ages, pregnant women and foetuses have been published (Christ et al, 2010b;Dimbylow & Bolch, 2007;Dimbylow, Nagaoka & Xu, 2009;Uusitupa et al, 2010). Further work, including modelling the SAR distribution at different gestational stages, is being pursued in several countries.…”
Section: Further Work On Dosimetric Models Of Children Of Different Amentioning
confidence: 99%
“…The effect on SAR of different dielectric properties between adults and children was examined in a few studies [22][23][24]. The variation in the dielectric properties with age is mainly due to the changes in the water content of tissues.…”
Section: Age and Dielectric Properties Of Tissuesmentioning
confidence: 99%
“…Christ et al [24] compared the SAR produced by three different phone models in anatomical head models of two adults and four children at different ages, together with agedependent dielectric properties of tissue, based on porcine data reported by Peyman et al [23]. The used phone models were a generic mobile phone equipped with a monopole antenna, a generic mobile phone with an integrated dual band antenna at the top of the body, and a CAD model of the Motorola Timeport T250 with a helical antenna.…”
Section: Age and Dielectric Properties Of Tissuesmentioning
confidence: 99%
“…It is robust, accurate, and well suited to studying problems involving highly inhomogeneous media, such as the human body. The FDTD method has been used numerous times to study human exposure to various radiating devices, e.g., cell phones [7][8][9][10][11][12][13], mobile-phone basestation antennas [14], Wi-Fi [15] and Bluetooth devices [16], and "electronic article surveillance" devices [17]. The FDTD method has also been extensively used to study exposure to plane waves, e.g., [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The SAR uncertainties from effects of age-dependent tissue variations [11], posture, and anatomical variations [18,25] have been studied previ ously, and are beyond the scope of the current analysis. How ever, we do wish to point out that [11] showed that age-dependent tissue variation had little effect on the peak spa tially average SAR value.…”
Section: Introductionmentioning
confidence: 99%